2020
DOI: 10.1038/s41377-020-0291-2
|View full text |Cite
|
Sign up to set email alerts
|

Saturable plasmonic metasurfaces for laser mode locking

Abstract: Metamaterials are artificial materials made of subwavelength elementary cells that give rise to unexpected wave properties that do not exist naturally. However, these properties are generally achieved due to 3D patterning, which is hardly feasible at short wavelengths in the visible and near-infrared regions targeted by most photonic applications. To overcome this limitation, metasurfaces, which are the 2D counterparts of metamaterials, have emerged as promising platforms that are compatible with planar nanote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(67 citation statements)
references
References 52 publications
1
66
0
Order By: Relevance
“…Wang et al investigated the SA properties of 2D plasmonic metasurfaces under the radiation of intensive laser by tailoring the input polarization and geometric parameters of metasurfaces. [239] When the nanorod arrays were embedded into the cavity, one could acquire a fairly stable modelocked lasing. This ultrathin saturable absorber can provide a versatile platform for supporting ultrafast laser.…”
Section: Saturable Absorption (Sa) and Lasermentioning
confidence: 99%
“…Wang et al investigated the SA properties of 2D plasmonic metasurfaces under the radiation of intensive laser by tailoring the input polarization and geometric parameters of metasurfaces. [239] When the nanorod arrays were embedded into the cavity, one could acquire a fairly stable modelocked lasing. This ultrathin saturable absorber can provide a versatile platform for supporting ultrafast laser.…”
Section: Saturable Absorption (Sa) and Lasermentioning
confidence: 99%
“…Recently, plasmonic metasurfaces made of an array of GNRs for which plasmonic properties are well established are designed and fabricated, as shown in Figure a. [ 105 ] According to the measurements of NLO response, this plasmonic metasurface demonstrated saturable absorption in the NIR region and the NLO response is polarization dependent. The authors further demonstrated that the plasmonic metasurfaces could be used as SAs with modulation performances superior to that of other 2D materials, which can reach values as high as M d = 60%, as shown in Figure 7c.…”
Section: Plasmonic Sas Based On Noble Metal and Non‐noble Metal Systemsmentioning
confidence: 99%
“…[26,27] These capabilities can be further extended or improved by introducing nonlinearity into metamaterials and metasurfaces. [28][29][30][31] For example, nonlinear metasurface absorbers [32][33][34][35] permit the transmission of low-amplitude signals used for antenna communications while effectively absorbing strong electromagnetic noise that may affect sensitive electronics even at the same frequency, as opposed to linear metasurface absorbers, which accept both types of waves. Recently, circuit-based metasurfaces containing nonlinear Schottky diodes have been reported to discriminate particular electromagnetic waves at the same frequency depending on their waveforms, or more specifically, their pulse widths.…”
Section: Doi: 101002/adts202000187mentioning
confidence: 99%